A Study on the Drug Concentration in Fellow Eyes After Unilateral Intravitreal Injection of Conbercept Into New Zealand Rabbit Eyes - Di, Yu; Xu, Haiyan; Ye, Junjie; Guo, Zijian (Frontiers in Pharmacology, 2021)
Intravitreal injections of anti-vascular endothelial growth factor (VEGF) have become increasingly popular in the treatment of ocular diseases. However, few studies have determined the efficiency of unilateral intravitreal anti-VEGF injection in the fellow eye. Herein, we performed a study to investigate drug concentration in the fellow eyes and venous serum after unilateral intravitreal injection of conbercept into rabbit eyes.This is an experimental animal study. Thirty male New Zealand rabbits (60 eyes) were used. One eye of each rabbit was intravitreally injected with 0.5 mg of conbercept. Both eyes from 6 rabbits were enucleated on Days 1, 3, 7, 14, and 30. Conbercept concentrations were measured in the serum, aqueous humor and vitreous humor. We found conbercept was detected in the fellow eyes and serum of rabbits. Conbercept concentrations in the vitreous humor of the fellow eyes increased from 74.11 ng/ml on Day 1 to 246.69 ng/ml on Day 3, then declined to 69.11 ng/ml after 30 days. The concentration in the aqueous humor peaked on Day 1 with a concentration of 244.82 ng/ml and declined to 40.13 ng/ml after 30 days. The maximum conbercept concentrations in the aqueous humor and vitreous humor of fellow eyes were similar, which were 0.2% and 1.3% those of the injected eye, respectively. A peak concentration of 102.49 ng/ml was achieved in venous serum 1 day after intravitreal injection of conbercept, which was 0.08% and 0.5% those of the maximum conbercept concentrations in the vitreous humor and aqueous humor of the injected eye, respectively, and 41.5% and 41.8% of the maximum conbercept concentrations in the vitreous humor and aqueous humor of the noninjected eye, respectively. In conclusion, after intravitreal injection of 0.5 mg of conbercept into rabbit eyes, very small amounts of conbercept were detected in the fellow noninjected eyes and venous serum.